Model Pembelajaran Means-Ends Analysis dalam Menumbuhkembangkan Kemampuan Problem Solving dan Productive Disposition - Andi Aras (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2020)
Abstract:The problem solving and productive disposition ability of students is still low due to the inaccuracy of the learning model used by teachers in learning mathematics. This study aims to determine the effectiveness of the Means-Ends Analysis (MEA) learning model in developing students' problem solving and productive disposition abilities. This type of research is pre-experimental research with One-Group Pretest-Posttest Design. The data analyzed are the results of students' mathematical problem solving and productive disposition data of students after learning using the Means-Ends Analysis (MEA) learning model. From the results of this study, it can be seen that the Means-Ends Analysis (MEA) learning model is effective in developing students' problem solving and productive disposition abilities with the effectiveness criteria: (1) The results of students' problem-solving abilities are categorized to be effective both descriptively and inferentially in terms of posttest scores, normalized gain, and classical completeness. (2) The productive disposition of students is categorized effectively both descriptively and inferentially in terms of the score of productive disposition and increase in productive disposition. Abstrak:Rendahnya kemampuan problem solving dan productive disposition peserta didik disebabkan oleh ketidaktepatan model pembelajaran yang digunakan oleh guru dalam pembelajaran matematika. Penelitian ini bertujuan mengetahui keefektifan model pembelajaran Means-Ends Analysis (MEA) dalam menumbuhkembangkan kemampuan problem solving dan productive disposition peserta didik. Jenis penelitian yang digunakan adalah pre-experimental dengan desain One-Group Pretest-Posttest Design. Data yang dianalisis adalah hasil problem solving dan productive disposition peserta didik setelah pembelajaran matematika dengan menggunakan Means-Ends Analysis (MEA). Dari hasil penelitian ini diperoleh bahwa Means-Ends Analysis (MEA) efektif dalam menumbuhkembangkan kemampuan problem solving dan productive disposition peserta didik dengan kriteria keefektifan: (1) Hasil kemampuan problem solving peserta didik dikategorikan efektif baik secara deskriptif maupun secara inferensial yang ditinjau dari: skor posttest, gain ternormalisasi, dan ketuntasan klasikal. (2) Productive disposition peserta didik dikategorikan efektif baik secara deskriptif maupun secara inferensial yang ditinjau dari: skor productive disposition dan peningkatan productive disposition.